Horizons of consciousness (Journal of Philosophy Culture and Political Science, 2018)
This article puts forward the problem of consciousnessas one of the most fascinating and complicated issues ofboth contemporary science and philosophy. It considerssome methodological respects, necessary for the furtherstudy of consciousness.